Retracted: INTEGRASI PAJAK DAN ZAKAT DI INDONESIA PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - El-Jizya, Editor (el-Jizya: Jurnal Ekonomi Islam, 2019)
This paper was retracted by Fakultas Ekonomi dan Bisnis Islam as Publisher on August 8, 2019. This paper was published due to a technical error and was not intended to be included in this journal. This article is the property of Masnun Tahir & Zasiana Elly Triantini, which has been published in the journal Al-Adalah Faculty of Sharia UIN Raden Intan Lampung volume 12 number 1 in 2015 at http://ejournal.radenintan.ac.id/index.php/adalah/article/view/204/374. Thus the article belongs to Moh. Abdur Rohman Wahid was not published by us. Retractions are published on August 8, 2019.